The Study of Industrialized Building System (IBS) Implementation in Terrace Housing Project - Jing Le, Leong; Zainal, Rozlin (Research in Management of Technology and Business, 2021)
In the era of globalization, Malaysia has adopted a construction technology in the construction sector under the term “Industrialized Building System” or “IBS”. The application of IBS is to address the problem of high demand of housing in Malaysia. The housing project in Malaysia has play a significant role in contribute the construction industry and growing the economics of Malaysia. IBS were facing some issue when implemented it such as lack of financial project, lack of knowledge, equipment, and machinery. The purpose of this study is to identify the types of IBS, the challenges of IBS implementation and the strategies of IBS implementation in terrace house project. 5 construction company experience in IBS was the target respondent in this research. Qualitative research conducted in this research. Semi-structured interview used to collect data. Content analysis was using in this research to analysis data has been collected. Through the data research, its show that the steel formwork system is the most applied among the respondent. Besides, high capital investment was one of the biggest challenges faced by the contractor and provide training and development program can be the strategies to make sure the employees are qualified to manage the construction project by using the IBS application. In conclusion, the research help and encourage more construction players and beneficial to the contractor in better understanding about IBS.